Trade and the environment: an empirical analysis - (:unkn) unknown (My University, 2025)
The project aims at providing orders of magnitude regarding the relationship between trade and polluting emissions at the world-wide level. Overall, the obtained results suggest that trade is not necessarily bad for the environment. One reason to worry is that differences in environmental regulations seem to motivate dirty production to locate in countries with weak environmental standards (usually poor countries). However, this effect is often more than counterbalanced by the opposite force arising from the fact that dirty goods are capital-intensive, which provides a comparative advantage to capital-rich countries, where environmental standards are high. Regarding SO2 emissions, it is shown that trade contributed, although modestly, to the recent decline in global emissions by allowing, on average, the cleanest countries to specialize in the production of dirty goods. Finally, CO2 per capita emissions, which diverge between countries at the global level, tend to converge within members of preferential trade areas, although the precise role of trade in this context has still to be clarified.
Keywords: trade; environment; pollution haven; growth decomposition; convergence